P43 POEMS neuropathy in the rheumatology clinic. (20th April 2020) - Waters, Lisa; Benson, Rosalind; Mahindrakar, Madhu; Moots, Robert; Abernethy, Rikki
Abstract: Background: POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, skin changes) is a rare, disabling, auto-inflammatory condition that may present to multiple specialties including rheumatology. We describe a case fulfilling all diagnostic criteria. Methods: Please refer to the results section. Results: A 52 year old lady of Venezuelan origin was referred to the rheumatology clinic with myalgia and arthralgia. She had a recent diagnosis of hypothyroidism. Her main concern was of skin hyperpigmentation, hypertrichosis and a reticular rash. She had been diagnosed with undifferentiated connective tissue disease (CTD) in Panama and had received a good symptomatic response to IM depomedrone. Initial examination findings revealed generalised skin pigmentation, hyperaemia and limited weakness of both shoulders. There were no other features of CTD. Initial bloods revealed normal FBC, UE, LFTS, CRP 18mg/l and ESR 37mm/hr. Serum electrophoresis, immunoglobulins, CK, cortisol, calcium, TSH, ANCA and urinalysis were normal. ANA was normal but had previously been positive in Panama. MRI of spine showed multiple abnormalities consistent with bony metastases. CT of chest, abdomen and pelvis (CAP) confirmed changes consistent with widespread sclerotic bony metastases with bilateral axillary lymphadenopathy, splenomegaly and diffuse bladder wall thickening. Lymph node biopsy confirmed Castleman-like changes, but this was not pathognomonic. Thyroid biopsy showed reactive changes. A bone biopsy of a sacral lesion revealed haemangioma. A PET scan highlighted sclerotic lesions and splenomegaly only. Mammogram and cystoscopy were normal. She then presented via ophthalmology to the acute medical unit at a different hospital with visual disturbance and confirmed papilloedema. CT head was normal. Lumbar puncture confirmed high CSF pressure and high protein levels of 1.75g/l. MRI of brain with enhancement showed leptomeningeal enhancement felt to be post-lumbar puncture change. Repeat CT CAP showed mild ascites and splenomegaly. Extensive infectious disease tests were all negative including HIV and TB Quantiferon. A review of medical literature and input from radiologists raised the diagnosis of POEMS. Immunofixation was requested and this confirmed a low level IGA lamba monoclonal band. Vascular endothelial growth factor was significantly elevated at 4800. Bone marrow biopsy confirmed low level lambda restricted plasma cell infiltration consistent with POEMS. She is now being treated with Lenalidomide and dexamethasone under the care of haematology and is likely to require an autologous stem cell transplant in the future. Conclusion: The challenge of diagnosing POEMS is well recognised. Few patients meet the full criteria for diagnosis. The heterogeneity of its clinical presentation means that patients may present to several specialities with multiple complaints. The combination of musculoskeletal symptoms, skin changes and inflammatory neuropathy may give rise to a rheumatology opinion and therefore it is important rheumatologists have awareness of the condition. We recommend that POEMS should be considered in patients presenting with an inflammatory neuropathy. Disclosures: L. Waters None. R. Benson None. M. Mahindrakar None. R. Moots None. R. Abernethy None.